Analysis of Extrinsic Factors on the Incidence of Pneumonia in Toddlers in the Working Area of the Batu Aji Community Health Center, Batam City in 2022 - Didi Yunaspi; Roza Erda; Melini Basridiyanti (Nusantara Science and Technology Proceedings, 2024)
Pneumonia is an acute infection that causes the lungs to become inflamed. Pneumonia is the main cause of death of children under five in the world. This disease accounts for 16% of all deaths of children under 5 years, which causes the deaths of 920,136 children under five, or more than 2,500 per day. If prevention is not carried out, there will be around 11 million child deaths worldwide by 2030. Prevention efforts are a component The most strategic way to eradicate pneumonia in toddlers consists of immunization and non-immunization prevention. Actions that are no less important are non-immunization prevention by carrying out preventive efforts such as improving nutrition with healthy nutrition, preventing pollution in the environment, and providing exclusive breastfeeding. This study aims to look at the factors associated with the incidence of pneumonia in toddlers in the Batu Aji Community Health Center Working Area, Batam City in 2022. This research is an analytical study with a cross-sectional design. The respondents in this study were 56 mothers of toddlers. The sampling technique used was non-probability sampling, namely purposive sampling. Data collection techniques were carried out through questionnaires and medical records. The results of statistical tests using Mann Whitney showed that of the 11 variables, 8 variables had a significant relationship with the incidence of pneumonia, while 3 variables, namely maternal age, maternal education, and family economic status, did not have a significant relationship with the incidence of pneumonia. It is hoped that health workers will carry out IMCI examinations to reach targets of diseases suffered by toddlers and provide health education about the factors that cause pneumonia, prevention, and treatment of pneumonia.